Prominent Dutch American entrepreneurs : their contributions to American society, culture and economy - Pegels, C. Carl (Emerald Publishing Limited : Information Age Publishing, 2011)
The book presents the stories of the more successful Dutch American entrepreneurs, active in the United States, with some going back as far as 400 years. The majority of the entrepreneurs covered in the book were active during the past 150 years. Each of the individuals covered represent an enterprise that was well known during its respective era. In some of the cases the individuals were better known than the enterprises they represented, and some became historic figures.Some of the more famous Dutch American entrepreneurs are Cornelius Vanderbilt, and his son William Vanderbilt, transportation entrepreneurs in the nineteenth century. Also famous during the early nineteenth century was DeWitt Clinton, the driving force behind the building of the Erie Canal. During the twentieth century, there were such famous Dutch American entrepreneurs as Cecil B. DeMille, Darryl Zanuck, and others in the entertainment industry. The most successful entrepreneurs, still alive today, are the billionaire businessmen, the Koch brothers, who own the multibillion dollar Koch Industries, an oil and chemical industry firm.The book's audience consists of academics, the public, and specifically the Dutch American public, numbering from 6 to 10 million people. The book is also an important source book and reader for college courses in Entrepreneurship, American History, Culture, Society and Economy.
Keywords: Businessmen -- United States -- Biography.; Entrepreneurship -- United States -- History.; Dutch Americans -- Biography.; elektronické knihy; Biographies.; Biography & Autobiography -- Business.; Biography: business and industry.; electronic books